2001
DOI: 10.1074/jbc.m007609200
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Angiogenesis in Vivo by Plasminogen Activator Inhibitor-1

Abstract: The process of angiogenesis is important in both normal and pathologic physiology. However, the mechanisms whereby factors such as basic fibroblast growth factor promote the formation of new blood vessels are not known. In the present study, we demonstrate that exogenously added plasminogen activator inhibitor-1 (PAI-1) at therapeutic concentrations is a potent inhibitor of basic fibroblast growth factor-induced angiogenesis in the chicken chorioallantoic membrane. By using specific PAI-1 mutants with either t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
150
0
3

Year Published

2002
2002
2010
2010

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 160 publications
(164 citation statements)
references
References 63 publications
11
150
0
3
Order By: Relevance
“…Consistent with this, tumor angiogenesis and invasion were observed in vitronectin-deficient mice as well as in wild-type mice [92]. In a separate study using PAI-1 mutants, the inhibition of bFGF-induced angiogenesis in the CAM assay required both the anti-proteinase activity as well as the vitronectin-binding capacity of PAI-1 [98]. Together, these data suggest that depending on the situation, PAI-1 may control angiogenesis by regulating proteolytic and/or nonproteolytic events in endothelial cell migration.…”
Section: Unexpected Role Of Pai-1 In Tumor Angiogenesissupporting
confidence: 62%
See 1 more Smart Citation
“…Consistent with this, tumor angiogenesis and invasion were observed in vitronectin-deficient mice as well as in wild-type mice [92]. In a separate study using PAI-1 mutants, the inhibition of bFGF-induced angiogenesis in the CAM assay required both the anti-proteinase activity as well as the vitronectin-binding capacity of PAI-1 [98]. Together, these data suggest that depending on the situation, PAI-1 may control angiogenesis by regulating proteolytic and/or nonproteolytic events in endothelial cell migration.…”
Section: Unexpected Role Of Pai-1 In Tumor Angiogenesissupporting
confidence: 62%
“…Addition of exogenous recombinant PAI-1 at a physiological concentration restores microvessel sprouting, while at 'therapeutical' concentrations, angiogenesis is inhibited [96]. Similarly, PAI-1 inhibits bFGF-induced angiogenesis when added at high concentrations [98]. Thus PAI-1 appears to have a dual function displaying pro-an-giogenic activity at physiological concentrations and anti-angiogenic effects at high, pharmacological concentrations.…”
Section: Unexpected Role Of Pai-1 In Tumor Angiogenesismentioning
confidence: 98%
“…To date, various proteins of the SERPIN family including cleaved AT, 32 PAI-1, 35 and PEDF 36 have been reported to inhibit angiogenesis. In the present study, we compared the anti-angiogenic activity among various SERPIN proteins using in vitro tube formation assay, and found that PCI strongly inhibits angiogenesis, this anti-angiogenic effect being almost similar to that of cleaved AT.…”
Section: Discussionmentioning
confidence: 99%
“…Purified serpins are as follows: PAI-1 (Molecular Innovations, Southfield, MI); PCI (human wild type recombinant PCI was expressed in Escherichia coli, strain BL21(DE3)pLysS, using the Qiagen pET15b expression vector (with an N-terminal polyhistidine sequence), and purified to homogeneity by Ni 2ϩ -chelate chromatography); 2 ␣ 2 -antiplasmin (Calbiochem); antithrombin III (ICN Biomedicals, Irvine, CA); ␣ 1 -proteinase inhibitor (generous gift from Annemarie Ralston, American Red Cross); ␣ 1 -anti-chymotrypsin (Athens Research and Technology, Athens, GA); and heparin cofactor II (46). PAI-1 mutant serpins used are as follows: PAI-1 A (R346A) and PAI-1 R (T333R/A335R) (47). PCI mutant serpins were P 1 -PCI (R355A) and P 14 -PCI (T342R).…”
Section: Methodsmentioning
confidence: 99%